In-situ mass-spectrometer of magnetized plasmas. (August 2017) - Sorokin, I.A.; Vizgalov, I.V.; Kurnaev, V.A.; Brandt, C.; Kreter, A.; Linsmeier, Ch.
Highlights: In-situ mass spectrometry in linear plasma device PSI-2. Deuterons dominate over molecular ions in deuterium plasma under standard discharge conditions. Fraction of double charged ions increases with discharge power in noble gas plasmas. Abstract: Modified mass-spectrometer of magnetized plasmas (MSMP-03) was installed on the linear plasma device PSI-2 in support of plasma-material interaction studies. MSMP-03 was adapted for in-situ mass-spectrum measurements in high-power discharge regimes and equipped with advanced measurements system consisting of a double-collector system allowing to decrease both the secondary electron emission signal in the high-voltage measurement range and the influence of the angular distribution of ions. To verify the MSMP-03 functionality, measurements of plasma ions mass-spectra were carried out for different working gases and discharge conditions in PSI-2. Mass-spectra of deuterium, argon, helium and neon plasma at the edge of the plasma column for different discharge conditions are presented.